Penerapan Algoritma dalam Pembuatan Kopi Berdasarkan Metode Penyeduhan Manual Brewing dan Fotografi Komersial - Roslina Sahara; Yahfizham Yahfizham (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
The level of coffee consumption has increased from year to year, which can be seen from the number of coffee shops that continue to appear with relatively large numbers of visitors. Coffee shops compete with each other to find coffee variants to become their mainstay menu. Please note that making coffee has various manual brewing methods, such as the Aeropess, V60, Kalita, Aeropress and French Press brewing methods. Many brewing methods require knowledge to practice them. So by creating a game that includes how to make coffee using manual brewing techniques and doing commercial photography a day, it is an incentive for coffee sales. Photography here plays a very important role in the world of advertising in order to get attractive visuals to attract the interest of potential consumers. The work creation method is used to produce work that suits the purpose to be conveyed. The process of exploration and improvisation with manual coffee brewing objects will be collaborated without eliminating the main functional aspects. Through the final task of creating this product photography work, produce commercial photos that are able to make the wider community more familiar with manual coffee brewing products which are usually available in coffee shops and help those who don't know how to brew coffee using manual brewing techniques, and can also as initial capital for young people who want to become baristas to complete the stages of making coffee using the Manual Brewing.